1990
DOI: 10.1017/s0952523800000730
|View full text |Cite
|
Sign up to set email alerts
|

Effects of synaptic blocking agents on the depolarizing responses of turtle cones evoked by surround illumination

Abstract: The effects of synaptic blocking agents on the antagonistic surround of the receptive field of cone photoreceptors were studied by intracellular recording in the retina of the turtle (Pseudemys scripta elegans). Illumination of a cone's receptive-field surround typically evoked a hybrid depolarizing response composed of two components: (1) the graded synaptic feedback depolarization and (2) the prolonged depolarization, a distinctive, intrinsic response of the cone. The locus of action of synaptic blocking age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(83 citation statements)
references
References 64 publications
5
78
0
Order By: Relevance
“…At higher concentrations, cobalt abolished the entire light response (Fig. 3A, inset, 300 M), presumably by interfering with calcium-dependent photoreceptor synaptic transmission (Thoreson and Burkhardt, 1990). For this cell, 150 M provided a good balance between these two extremes (Fig.…”
Section: Cobaltmentioning
confidence: 86%
See 1 more Smart Citation
“…At higher concentrations, cobalt abolished the entire light response (Fig. 3A, inset, 300 M), presumably by interfering with calcium-dependent photoreceptor synaptic transmission (Thoreson and Burkhardt, 1990). For this cell, 150 M provided a good balance between these two extremes (Fig.…”
Section: Cobaltmentioning
confidence: 86%
“…In outer retina, the antagonistic surround of the cone is blocked by cobalt in monkey (Verweij et al, 2003) and turtle (Thoreson and Burkhardt, 1990) and by carbenoxolone in monkey (Verweij et al, 2003) and teleost fish (Kamermans et al, 2001). The responses of horizontal cells to large flashing spots are also affected by both drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of kainate and CNQX were assessed by comparing the amplitude of the first signal obtained in the absence of drug with the second signal obtained in its presence. GABA blockers were not used routinely because picrotoxin had no significant effect on the second of the paired stimuli using either kainate (ϳ15% reduction, n ϭ 9; p Ͼ 0.05) or CNQX (ϳ10% reduction; n ϭ 7; p Ͼ 0.05), and it does not appear that GABA mediates feedback (Thoreson and Burkhardt, 1990;Verweij et al, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…O'Bryan (1973), Gerschenfeld and Piccolino (1980) and Burkhardt et al (1988) described Ca 2+ -dependent depolarizations which sometimes led to spikes in turtle cones, responses that were elicited by flashes of annular illumination in the presence of steady central illumination or by current injection into cones. Thoreson and Burkhardt (1990) found that the depolarizing responses in cones elicited by current injection were blocked by submicromolar concentrations of cobalt, suggesting that they depended on calcium. The same low concentrations of cobalt are sufficient to block the surround responses of bipolar cells without attenuating the response to central illumination (Vigh and Witkovsky, 1999).…”
Section: Feedback From Horizontal Cells To Conesmentioning
confidence: 98%
“…Calcium-dependent chloride currents contribute to depolarizing surround responses when the cone membrane potential is below E Cl (Thoreson and Burkhardt, 1990). E Cl in cones appears to be near or slightly negative to the dark resting potential (Kaneko and Tachibana, 1986;Thoreson and Burkhardt, 1991;Kraaij et al, 2000;Thoreson and Bryson, 2005) but in the presence of background illumination, the cone membrane potential often passes below E Cl .…”
Section: Feedback From Horizontal Cells To Conesmentioning
confidence: 99%